Fourteen years of Nepal Journal of Neuroscience - Roka, Yam Bahadur (Nepal Journal of Neuroscience, 2018)
Nepal Journal of Neuroscience (NJNS) was started in 2004 with its office in Department of Neurosurgery, Tribhuvan University Institute of Medicine. It was started as a biannual publication and remained so till 2017 when the number was increased to 3/year. This study aims to find the patterns of publication and topics since its inception to present. A total of 257 articles were published within this study period. This gives an average of 18.3 articles/ year with range from 9-32 articles/year.Considering the type of article published, the majority were original articles (90). Followed closely by case reports (87), review articles (29), editorial (18), neuro view box (19) and others. The parent country of origin, i.e. Nepal remains the largest contributor to the journal with 193 articles, followed by India (23), USA (9), Japan (7) and UK and Bangladesh (6 each). NJNS is the only platform in Nepal for neurosciences to showcase their research which will help to collect the nation-wide data and will in the long-term help to formulate rules and regulations, where applicable, to control and implement the various findings. I thus request all readers and well-wishers to continue their support to NJNS to make it one of the foremost research journal in neurosciences not only from Nepal but in the region.Nepal Journal of Neurosciences 15:6-9, 2018